Enhanced Torsion Mechanism of Small-Scale Reinforced Concrete Beams with Spiral Transverse Reinforcement - Shereen Mahmoud; Ahmed Youssef; Hamed Salem (Civil Engineering Journal, 2022)
The nonlinear torsional behaviour of small-scale reinforced concrete (RC) beams with continuous staggered spiral as transverse reinforcement stirrups is experimentally investigated. Twelve miniatures RC beams were tested under torsion load considering the closed shape of stirrups and compared with continuous staggered spiral ones. All miniatures beams were scaled down to be one-eighth the prototype beam size. The main parameters considered in this research are stirrup spacing and its configurations. Small scale RC beams were taken into account in the existing study because of their construction simplicity and financial feasibility. Mortar without coarse aggregate was applied instead of concrete to reduce the size effect of applying small scale models. Ongoing research trials have been carried out to obtain an efficacious approach to boost torsion failure mechanisms because brittle torsion failure of RC structural elements should be avoided. This study emphasized boosted torsion capacity, dissipated energy, and helical crack propagation. During testing, the primary cracking torsion moment, ultimate torsion moment, peak twist angle, and failure mechanism of the beams were inspected. The use of spiral stirrups showed great enhancement of the torsional behaviour of samples. It was observed that using spiral stirrups rather than closed stirrups could result in a substantial increase in torsion capacity and dissipated energy of 87.7% and 89.8%, respectively. As a result, the predicted capacities of the RC beams prototype were estimated in detail, taking account the scale down factor implemented by the authors. Values obtained based on international specifications and guidelines were used to compare the experimental results. Doi: 10.28991/CEJ-2022-08-11-019 Full Text: PDF